The Transition Of Legal Modernism Paradigm To Legal Postmodernism In The Digital Era - Setyawan, Vincentius Patria; Kurniawan, Itok Dwi (JUSTISI, 2022)
Abstract: Legal construction in Indonesia, which is largely influenced by the influence of the Continental European legal system, the Dutch heritage is identical with the nuances of legal positivism. The flow of legal positivism is in legal modernism, which is included in the form of written rules. The development of human civilization in modern times is so fast and gives birth to a modern digital civilization. The power of legal positivism is strong enough to solve legal problems that develop following the civilization of its people. The new paradigm that can be a solution to problems in this digital era is the post-modernism paradigm. Post-modernism opens up opportunities for diversity in the meaning of law. Rigid written law can be interpreted more flexibly with the context, so that within the framework of that meaning it becomes more flexible in solving problems that occur in society. Keywords: Modernism, Post-Modernism, Digital Era. Â 